Evaluation of Filtered Spark Gap on the Lightning Protection of Distribution Transformers: Experimental and Simulation Study - Pourakbari Kasmaei, Mahdi; Mahmood, Farhan; Krbal, Michal; Pelikán, Luděk; Orságová, Jaroslava; Toman, Petr; Lehtonen, Matti (MDPI, 2020)
Protection of transformers, as one of the most expensive equipment in the power system, against lightning overvoltage impulses is a vital task. This paper, for the first time so far, investigates the effects of a filtered spark gap on the protection level of transformers against lightning overvoltage impulses. The filter is an inductor that is placed in series with the transformer and before the spark gap aiming to reduce the voltage at the connection point of the spark gap, and hence, enhancing the protection level of the transformer under lightning overvoltages. The experimental laboratory tests are accomplished on a 400 kVA, 22/0.4 kV, Delta-Star (Delta-Y) connection type transformer under 110 kV, and 125 kV overvoltage impulses, whereas the size of the spark gap is set to 80 mm and two inductors of 35 mu Hand 119 mu Hare considered. In order to perform a more in-depth analysis, a model that works reasonably close to the empirical case is developed in the EMTP-RV software. An optimization algorithm is used to determine the sensitive parameters of the double-exponential function, which is used to reproduce the applied laboratory lightning impulse voltages in the EMTP-RV environment. Moreover, the transformer is modeled according to the Cigre Guidelines (Working Group 02 of Study Committee 33). The behavior of the spark gap is simulated as close as the practical situation using the disruptive effect method. The preciseness of the simulated filtered spark gap model is verified by comparing the results of the simulated model in the EMTP-RV with the results of experimental tests. After verifying the model, different sizes of inductors are studied in the EMTP-RV environment to investigate whether larger or smaller inductors provide better protection for the transformer under lightning conditions. A comparison is performed among the conventional spark gap, surge arrester, and the filtered spark gap to provide a better analysis of the potential of the proposed device. The results indicate that proper sizing of the inductor, within an effective range, slightly enhances the protection level of the transformer.

Protection of transformers, as one of the most expensive equipment in the power system, against lightning overvoltage impulses is a vital task. This paper, for the first time so far, investigates the effects of a filtered spark gap on the protection level of transformers against lightning overvoltage impulses. The filter is an inductor that is placed in series with the transformer and before the spark gap aiming to reduce the voltage at the connection point of the spark gap, and hence, enhancing the protection level of the transformer under lightning overvoltages. The experimental laboratory tests are accomplished on a 400 kVA, 22/0.4 kV, Delta-Star (Delta-Y) connection type transformer under 110 kV, and 125 kV overvoltage impulses, whereas the size of the spark gap is set to 80 mm and two inductors of 35 mu Hand 119 mu Hare considered. In order to perform a more in-depth analysis, a model that works reasonably close to the empirical case is developed in the EMTP-RV software. An optimization algorithm is used to determine the sensitive parameters of the double-exponential function, which is used to reproduce the applied laboratory lightning impulse voltages in the EMTP-RV environment. Moreover, the transformer is modeled according to the Cigre Guidelines (Working Group 02 of Study Committee 33). The behavior of the spark gap is simulated as close as the practical situation using the disruptive effect method. The preciseness of the simulated filtered spark gap model is verified by comparing the results of the simulated model in the EMTP-RV with the results of experimental tests. After verifying the model, different sizes of inductors are studied in the EMTP-RV environment to investigate whether larger or smaller inductors provide better protection for the transformer under lightning conditions. A comparison is performed among the conventional spark gap, surge arrester, and the filtered spark gap to provide a better analysis of the potential of the proposed device. The results indicate that proper sizing of the inductor, within an effective range, slightly enhances the protection level of the transformer.
Evaluation of Filtered Spark Gap on the Lightning Protection of Distribution Transformers: Experimental and Simulation Study
Keywords: disruptive effect; filtered spark gap; lightning overvoltage; surge arrester; transformer protection; disruptive effect; filtered spark gap; lightning overvoltage; surge arrester; transformer protection